Question and answer
What role do z-scores play in this transformation of data from multiple distributions to the standard normal distribution?
Transforming to a z-score allows you to use a single table (Standard Normal) to evaluate probabilities. Without the transformation, you would have to use calculus to determine the probabilities for each non-Normal distribution. [ ]
Expert answered|experto|Points 388|
Question
Asked 8/8/2013 6:00:37 PM
0 Answers/Comments
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
19,144,553 questions answered
Popular Conversations
The slope of the line whose equation is 5x + 3y = -2 ...
Weegy: The slope of the line whose equation is 5x + 3y = -2 is a.) -5/3 User: The y-intercept of the line whose ...
1/24/2015 10:20:25 PM| 6 Answers
What is the value of b^2 - 4ac for the following equation? 2x^2 - 2x ...
Weegy: 10x^2 - 19x + 6 = 0 The solution formula is x = [-b ? sqrt (b^2 - 4ac)]/2a The numerators of the solution is: ...
1/24/2015 9:48:19 AM| 4 Answers
Which of the following constants can be added to x^2 - 3x to form a ...
Weegy: 8x^2 - 2x = 1; 8x^2 - 2x - 1= 0; (4x + 1)(2x - 1) = 0 (4x + 1) = 0; 4x = -1, x = -1/4 or (2x - 1) = 0; 2x = 1; ...
1/24/2015 9:39:47 AM| 3 Answers
Which of the following points is a solution to the system of ...
Weegy: The following points of(-3 , -2) is a solution to the system of equations shown y - x = -1 x + y = -5 . ...
1/24/2015 10:34:32 PM| 3 Answers
8y - 1 = x 3x = 2y Solve the system of equations by ...
Weegy: 2x + y = 6; y = 3x + 4 The resulting equation is 2x + (3x + 4) = 6. User: 2x + y = 7 y = x + 1 When the ...
1/24/2015 10:54:55 PM| 3 Answers
Brenda Lee has received a $10,000 gift from her mother and is trying ...
Weegy: B. return User: Terri Hamilton has just received $30,000 from an uncle who died and is trying to decide how to ...
1/24/2015 2:01:50 PM| 2 Answers
The graph of which of the following equations contains the points (2, ...
Weegy: 2x - y = 2 x + y = 4 3x = 6; x = 6/3; x = 2 2x - y = 2; 2(2) - y = 2; 4 - y = 2; -y = 2 - 4; -y = -2; y ...
1/24/2015 9:12:35 PM| 2 Answers
Weegy Stuff
S
L
Points 1635 [Total 1656]| Ratings 0| Comments 1635| Invitations 0|Offline
S
L
P
L
P
Points 1223 [Total 6500]| Ratings 0| Comments 1223| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
P
Points 563 [Total 15574]| Ratings 0| Comments 563| Invitations 0|Offline
S
L
Points 438 [Total 1119]| Ratings 2| Comments 418| Invitations 0|Offline
S
1
L
L
Points 170 [Total 6870]| Ratings 0| Comments 170| Invitations 0|Online
S
P
C
L
P
L
1
Points 90 [Total 6678]| Ratings 1| Comments 80| Invitations 0|Offline
S
Points 87 [Total 102]| Ratings 0| Comments 87| Invitations 0|Offline
S
L
Points 73 [Total 1634]| Ratings 0| Comments 73| Invitations 0|Offline
S
Points 63 [Total 445]| Ratings 0| Comments 63| Invitations 0|Offline
S
Points 50 [Total 52]| Ratings 0| Comments 0| Invitations 5|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.